Politics book : a lexicon of political facts from Abu Ghraib to Zippergate - Comfort, Nicholas (New Delhi, 2005)
A lexicon of interesting political facts, The Politics Book is a snapshot of where the language of Politics has got to. It has always been the richest of languages, because of the vivid way in which many of our politicians express themselves, from the sound-bites with which they woo the voters to the devastating put-downs they use on each other. If a week in politics is a long time, twelve years is an eternity. It is that long since Brewer's Politics, the precursor of this volume, first appeared, and in that time the lexicon has grown exponentially. From Abu Ghraib to Zippergate, words, phrases, concepts, movements and people of whom we could have had no conception in 1993 are now part of our heritage. Twelve years ago New Labour had yet to be born, sleaze was an American phenomenon, no European Commission had ever been removed, a presidential election decided by the Supreme Court seemed inconceivable, and a chain of terrorist atrocities on the scale of 9/11 even more so.
Keywords: Political facts-Lexicon